AI-driven information retrieval system for candidate screening - Silva, Vasco Reid Ferreira da (2024)
Efficient screening and evaluation in the recruitment process are tasks that demand substantial time and effort from Human Resources professionals. These processes often suffer from long waiting periods, inconsistent candidate evaluation, and the potential to overlook qualified candidates. In this context, leveraging state-of-the-art natural language processing architectures, specifically large language models (LLMs), holds significant promise. LLMs can generate evaluations using advanced prompt techniques to improve the accuracy and reliability of the output. This thesis researches the feasibility of employing 7 billion parameter LLMs in candidate screening to reduce response times, decrease workload, and improve evaluation consistency. The study involves a comparative analysis of various state-of-the-art large language models to identify those most suitable for this application. Additionally, it examines different prompt engineering techniques to optimize the performance of these models. A comprehensive analysis of the results is conducted to determine the most effective combinations of LLMs and prompt engineering techniques. This includes a two-way validation process, utilizing both the state-of-the-art GPT-4 model and manual human resources validation, to ensure the robustness and reliability of the findings. The outcomes of this thesis aim to enhance the quality of candidate screening by integrating LLMs into the process. Furthermore, this work aspires to provide valuable insights into the capabilities of 7 billion parameter large language models in the field of human resources and their application in real-world scenarios.